The synthesis and applications of cyclic alkenylsiloxanes - Elbert, B; Bryony Elbert (2014)
This thesis describes the development of robust methodology to access cyclic alkenylsiloxanes, and their subsequent application in Hiyama-Denmark cross couplings. An early chapter shows the identification of Lindlar reduction conditions capable of generating cyclic alkenylsiloxanes from alkynylsiloxanes in high yields. The use of such species in Hiyama-Denmark cross coupling is then examined, with particular emphasis on the development of fluoride-free conditions, previously unreported for this class of organosilane. A ring-size dependent orthogonality is revealed, where 5-membered cyclic alkenylsiloxanes cross couple under basic conditions, while 6-membered analogues are inert. The origins of this effect are investigated experimentally and theoretically, leading to the proposal of detailed mechanisms for coupling. In the final chapter, the methodology that has been developed is applied to total synthesis. The great potential of the orthogonality uncovered is demonstrated with the highly convergent construction of anti-inflammatory natural product resolvin D3 by sequential, one-pot, orthogonal cross couplings.